Forecasting the stock market using ARIMA and ARCH/GARCH approaches - Dinardi, Felipe Bardelli (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management